1973
DOI: 10.3382/ps.0521787
|View full text |Cite
|
Sign up to set email alerts
|

Pigmentation of Egg Yolks by Xanthophylls from Corn, Marigold, Alfalfa and Synthetic Sources

Abstract: Leghorn-type hens in cages and floor pens were used to evaluate pigmenting potential for producing table-egg and intensely colored egg yolks from the xanthophylls in corn gluten meal, alfalfa and marigold meal and for 0-apo 8' carotenal (BAC) and the carotenoic acid ethyl ester (BACE). There were no consistent differences in utilization efficiencies between corn gluten meal, 20% protein dehydrated alfalfa meal, a 40% protein alfalfa concentrate, total xanthophyll extracts of corn or alfalfa or BAC. Xanthophyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

1976
1976
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…The results for hens are in contrast with the earlier work of Guenthner et al (1973), which indicated the same xanthophyll availability from dehydrated alfalfa, xanthophyll extracts from dehydrated alfalfa, and a commercially prepared Pro-Xan. They also indicated lutein to be equal to or poorer than alfalfa as a pigmented Halloran (1972) also showed no difference in xanthophyll availability for a commercial Pro-Xan and dehydrated alfalfa for broilers and laying hens.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The results for hens are in contrast with the earlier work of Guenthner et al (1973), which indicated the same xanthophyll availability from dehydrated alfalfa, xanthophyll extracts from dehydrated alfalfa, and a commercially prepared Pro-Xan. They also indicated lutein to be equal to or poorer than alfalfa as a pigmented Halloran (1972) also showed no difference in xanthophyll availability for a commercial Pro-Xan and dehydrated alfalfa for broilers and laying hens.…”
Section: Discussioncontrasting
confidence: 84%
“…The poorer performance of the commercial Pro-Xan is probably explained by the more drastic conditions used in its preparation and drying. However, the reasons for the relatively poor response Guenthner et al (1973) obtained from lutein and xanthophyll extracts are not clear.…”
Section: Discussionmentioning
confidence: 95%
“…The evaluation of different feed ingredients and synthetic sources of xanthophyll has been extensively investigated by Sullivan and Holleman (1962); Guenthner et al (1973); and Fry et al (1974). The genetic capability to absorb and deposit xanthophylls in the egg yolk has been found to vary among individual hens within a single strain (Scott et al, 1968) and also between breeds of hens (Marusich et al, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…Many ingredients used in poultry feed contain high levels of xanthophyll, a natural pigment giving the egg yolk its characteristic yellow color (Guenthner et al, 1973). As the xanthophyll-containing ingredients are increased, so does the intensity of egg yolk color (Brambila et al, 1963).…”
Section: Introduction H Igh Feed Costs Have Resulted In a Searchmentioning
confidence: 99%